The music of Conlon Nancarrow - Gann, Kyle (Cambridge Cambridge University Press, 1995)
Conlon Nancarrow has written the most rhythmically complex music the world has ever known, so complex that it can only be realized on a mechanical player piano. Yet Nancarrow's whirlwinds of notes, sometimes as many as eighty per second, are jazzy and infectiously joyous. The music he composed in almost complete isolation from 1940 on has only recently achieved international fame, and this is the first book to cover in detail Nancarrow's life and compositional achievements. The book includes analysis of sixty-five works and previously unpublished biographical information.